Anxiety and emotion regulation in middle school students: the mediating role of subjective well-being and the buffering effect of physical activity - Xue, Wanchun; Chen, Chuan; Fan, Zhenying; Tang, Yanxia; Zhang, Jianhua (Frontiers in Developmental Psychology, 2026)
Background and ObjectivesThe impact of anxiety on adolescents' emotion regulation has been widely documented, yet the underlying mechanisms remain unclear—particularly the potential moderating role of physical activity (PA). This study aimed to develop a moderated mediation model to test whether anxiety influences emotion regulation via subjective well-being (SWB), and to examine whether physical activity moderates the paths from anxiety to subjective well-being and from anxiety to emotion regulation.MethodsUsing convenience sampling, we conducted a cross-sectional, self-administered survey in June 2025 among 2,500 middle school students. After screening, 2,354 valid questionnaires were retained (1,098 males; 1,256 females). Four core variables were measured: anxiety, subjective well-being, sleep hygiene, and physical activity. Pearson correlation coefficients were first computed to assess bivariate associations, followed by tests of mediation and moderation using the SPSS PROCESS macro (Models 4 and 8).ResultsAnxiety significantly and negatively predicted emotion regulation, and this association was partially mediated by subjective well-being. Anxiety significantly and negatively predicted subjective well-being, whereas subjective well-being significantly and positively predicted emotion regulation. Moreover, physical activity significantly moderated both the anxiety → subjective well-being and anxiety → emotion regulation paths, attenuating the adverse effects of anxiety.ConclusionsThis study elucidates the mechanism through which anxiety affects emotion regulation in adolescents, highlighting the mediating role of subjective well-being and the protective moderating effect of physical activity. The findings offer a new perspective for school- and family-based interventions, suggesting that integrating emotion-management strategies with regular physical exercise may enhance adolescents' emotion regulation and mental health.